2007
DOI: 10.1016/j.rmed.2007.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the effects of chronic disease management on quality-of-life in people with chronic obstructive pulmonary disease

Abstract: All chronic disease management projects for people with COPD involving primary care improved quality of life. In most of the studies, aspects of chronic disease management were applied to a limited extent. Quality of randomized-controlled trials was not optimal. More research is needed on chronic disease management programmes in patients with COPD across primary and secondary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 34 publications
0
43
1
Order By: Relevance
“…Nevertheless, no studies reported a deterioration in HRQL and also there seemed to be no relation with the COPD severity of the included population or the setting in which the program was implemented. The latter is in contrast with a previous review of Niesink and colleagues,48 concluding that improved HRQL resulting from COPD disease management is limited to programs that are (at least partly) implemented in primary care.…”
Section: Discussioncontrasting
confidence: 74%
“…Nevertheless, no studies reported a deterioration in HRQL and also there seemed to be no relation with the COPD severity of the included population or the setting in which the program was implemented. The latter is in contrast with a previous review of Niesink and colleagues,48 concluding that improved HRQL resulting from COPD disease management is limited to programs that are (at least partly) implemented in primary care.…”
Section: Discussioncontrasting
confidence: 74%
“…The positive impact of smoking cessation on mortality and morbidity is well established,13 but few studies have showed the relevant impact on HRQoL and readmission. Furthermore, HRQoL had been determined in several intervention studies to achieving management goals in COPD 29,30…”
Section: Discussionmentioning
confidence: 99%
“…A review by Niesink and colleagues (76) identified 10 education interventions, nine of which also included exercise training. Other elements of the programs included support, relaxation training, smoking cessation, breathing retraining, recreational activities and occupational therapy.…”
Section: Discussionmentioning
confidence: 99%